Metal Ion Selective Self‐Assembly of a Ligand Functionalized Polymer into [1+1] Macrocyclic and Supramolecular Polymer Structures via Metal–Ligand Coordination. Issue 1 (16th August 2019) - Xu, Xiaowen; Van Guyse, Joachim F. R.; Jerca, Valentin Victor; Hoogenboom, Richard
Abstract: The design and synthesis of polymer‐based metallomacrocycles relying on metal–ligand interactions remain a challenge in the polymer field. Instead of utilizing chemical reactions to synthesize macrocycles, a general approach is proposed to construct metallomacrocyclic structures through supramolecular self‐assembly of a specific macroligand with suitable transition metal ions. Therefore, a new ditopic macroligand (L ) consisting of PEG end‐capped with 2, 6‐bis(1, 2, 3‐triazol‐4‐yl)pyridine derivatives is prepared via CuAAC "click" reaction. Four types of metal (Fe 2+, Zn 2+, Ni 2+, and Cu 2+ ) complexes are obtained by simply mixing a solution of metal ions and L in appropriate concentrations. The investigation of the coordination chemistry suggests that coordination of L with Cu 2+ results in the formation of a [1+1] metallomacrocycle, while the other metal complexes exclusively lead to the formation of linear metallopolymers and/or larger aggregates. This work provides new insights into designing metallomacrocycles and may have potential application in the synthesis of catenanes and other cyclic or cycle‐based topological architectures. Abstract : A new ditopic macroligand is synthesized by end‐functionalization of poly(ethyleneglycol) with 2, 6‐bis(1, 2, 3‐triazol‐4‐yl)pyridine derivatives. The macroligand is coordinated with four metal ions (Fe 2+, Zn 2+, Ni 2+, and Cu 2+ ) to obtain metal complexes. The complex formation is investigated by UV–vis spectroscopy. Complexation of the macroligand with Cu 2+ results in a [1+1] metallomacrocycle, while the other metal complexes only result in larger aggregates.